DINAMIKA PERUBAHAN EKONOMI MAKRO DAN DAMPAKNYA TERHADAP PERTUMBUHAN PENERIMAAN PAJAK PENGHASILAN NON MIGAS - Mas'udin Mas'udin (JURNAL PAJAK INDONESIA, 2017)
This study examines the impact of macroeconomic on tax revenue, especially non-oil and gas income tax. The time period of study ranges from 1970 to 2016. The study was conducted to obtain empirical evidence of factors influencing the growth of non-oil tax revenues in Indonesia. The model was analyzed using Vector Auto Regressive. The VAR estimation shows that there is a one-way relationship between economic growth, inflation rate, exchange rate and non-oil and gas income tax. In the short term, shocks of non-oil and gas income tax is the factor with the greatest influence on the growth of non-oil tax. In the long run, exchange rate shocks, inflation, economic growth, ICP, and non-oil income tax incidence shocks affect the growth of non-oil and gas income tax. Studi ini mengkaji dampak ekonomi makro terhadap penerimaan perpajakan, khususnya pajak penghasilan non migas. Rentang periode kajian selama 46 tahun yaitu dari 1970 s.d 2016. Studi dilakukan guna mendapatkan bukti empiris faktor-faktor yang mempengaruhi pertumbuhan penerimaan PPh non migas di Indonesia. Model dianalisis dengan menggunakan Vector Auto Regressive.  Hasil estimasi VAR menunjukkan terdapat hubungan satu arah antara pertumbuhan ekonomi, tingkat inflasi, nilai tukar rupiah dan PPh non migas. Dalam jangka pendek, guncangan (shock) PPh non migas merupakan faktor dengan pengaruh terbesar pada pertumbuhan PPh non migas itu sendiri. Dalam jangka panjang guncangan kurs, inflasi, pertumbuhan ekonomi, ICP, dan guncangan PPh non migas berpengaruh terhadap pertumbuhan PPh non migas.